Impacts of macroeconomics factors toward IDX composite and IDX finance during Covid-19 pandemic - Mei Siang Jemima Aurelia; Ranny Febrianti; Edwin Setiawan Nugraha (President University, 2022)
Macroeconomics is the branch of economy that deals with activity, structure, behaviour and decision making of economy as a whole. IDX Composite and IDX Finance are stock market indices used by Indonesia Stock Exchange, unfortunately, relationship between macroeconomics and IDX composite and IDX finance during COVID-19 period in Indonesia is still poorly understood. This research aimed to investigate the impacts of macroeconomics factor included Inflation Rate, Bank Indonesia rate (BI Rate), the exchange rate on IDR, and monthly new cases of COVID-19 in Indonesia on IDX Composite and IDXFINANCE, respectively. The analysis was using multiple linear regression method. The result indicated that BI Rate negatively significantly impacted both IDX Composite and IDXFINANCE. While, Indonesian inflation and USD to IDR exchange rate, gave significant impact on IDX Composite, consecutively positively and negatively. Partial test indicated that COVID-19 monthly cases in Indonesia did not impact both IDX Composite and IDXFINCANCE. In addition, Indonesian inflation and USD to IDR exchange rate also did not impact IDXFINANCE. Overall test illustrated that all of the mentioned macroeconomics variables impacted both IDX Composite and IDXFINANCE. This research is expected to help investors and traders in making futures investment decision.